Gas Chromatographic Analysis of Complex Sesquiterpenes in Malaysian Agarwood Essential Oil - M. M., Yusoff; Saiful Nizam, Tajuddin (2015)
Aquilaria malaccensis species is widely distributed in south and south-east Asia. It is a large evergreen tree which sometimes produces resin impregnated heartwood that is fragrant and highly valuable called agarwood. Formation of agarwood is believed to occur in the trunk and roots of trees that have been infected. As a response, the tree produces a resin high in volatile organic compounds that aids in suppressing or retarding the infection. In natural forests only about 7% of the trees are infected. Minor differences in the composition of agarwood essential oils can significantly alter product odor or flavor. For this reason, careful extraction and analysis of its essential oil components is important to ensure product consistency over time. There is very little information on the quality of different agarwood essential oils produced. The profile of hydro distilled agarwood essential oil is dominated by sesquiterpenes.